Optimizing collagen yields from lumpfish (Cyclopterus lumpus) skin Development of pre-treatment and acid extraction protocols - Judith Maria Scheja 1983- (2024)
Ritgerð lokuð til 30.06.2027 Lumpfish (Cyclopterus lumpus) is a marine cold-water fish, distributed in the North Atlantic. Female lumpfish are being caught in Iceland for their roe (3000 tons total catch in 2023). Currently around 70 % of the total catch are treated as waste and discarded. The skin of lumpfish is rich in collagen and gives an opportunity to utilize and add value to an underutilized resource. Collagen is a biomaterial being used in biomedical and pharmaceutical industry, in cosmetics and as a food supplement. A growing commercial interest in collagen results in the need of alternative sources. Particularly, collagen of marine origin gains interest as it has similar properties to mammalian collagen. The collagen extraction process includes an alkali pre-treatment step to remove non-collagen proteins from the raw material, an acid extraction step, and some recovery steps following the extraction. The aim of this study was to optimize both the alkali pre-treatment and acid extraction conditions. Two experimental designs were performed to generate the optimal conditions for alkali pre-treatment with NaOH and acid extraction using acetic acid. The contents of protein and hydroxyproline removed from the skins during pre-treatment were used as a measure of the most effective pre-treatment condition. Collagen yield, hydroxyproline content and SDS-PAGE patterns of collagen were used to select the most promising extraction conditions with acetic acid. Combined conditions resulted in a collagen yield of 35.0 % (dry weight) with a purity of 92.13 %. The SDS-PAGE pattern showed typical Type-I collagen bands. Horgnkelsi (Cyclopterus lumpus) er kaldsjávartegund sem hefur útbreiðslu um Norður Atlandshaf. Kvenfiskurinn (grásleppa) er veidd hér á landi vegna hrognanna (3000 tonna heildarafli árið 2023). Um 70 % aflans meðhöndlaður sem úrgangur og er hent eftir að hrognin hafa verið nýtt. Roð hrognkelsa er ríkt af kollageni sem gefur tækifæri til nýtingar og aukinnar verðmætasköpunar á vannýttri auðlind. ...